Answer:
an = 3n - 4
Step-by-step explanation:
difference is 3 between each number
To find the nth term of an arithmetic sequence, we can use the following formula:
**an = a1 + d(n - 1)**
where:
* **an** is the nth term
* **a1** is the first term (in this case, 7)
* **d** is the common difference (in this case, 3)
* **n** is the term number
Therefore, the nth term of the sequence is:
**an = 7 + 3(n - 1)**
an = 7 + 3(n - 1)
an = 7 + 3n - 3
an = 3n - 4
For example, to find the 5th term:
* **n = 5**
* **an = 7 + 3(5 - 1)**
* **an = 7 + 3 * 4**
* **an = 7 + 12**
* **an = 19**
Therefore, the 5th term in the sequence is 19